Bantuan perencanaan dan sosialisasi desain Balai RW 06 Medokan Asri Barat Surabaya - Zakariya, Afif Fajar; Sunarya, Wendy; Susanti, Wiwik Dwi (Penamas: Journal of Community Service, 2025)
The Community Hall is a vital public space for the community, serving not only as a venue for government activities but also as a hub for educational, recreational, and interactive events. To better support community harmony, the Community Hall in Surabaya’s residential areas should be designed to be functional, comfortable, and aesthetically appealing. Architectural expertise plays a key role in creating an attractive, contextually appropriate design. This community service project focused on the architectural design process for the Community Hall in Medokan Asri Barat, Surabaya. The process included consultation, site analysis, architectural exploration, presentation, and design development. The design incorporates neo-vernacular architecture, blending traditional Indonesian elements with modern touches. The result received positive feedback from the community. A participatory design approach involving local residents was essential in creating a design that aligns with their preferences and needs. This collaborative effort ensures that the Community Hall is both functional and meaningful to the community it serves.